Predictive modelling of vehicle speeds while traversing modern roundabouts based on geometric design characteristics - Arries, Jared Tyrell (Stellenbosch : Stellenbosch University, 2025)
Arries, J. T. 2025. Predictive modelling of vehicle speeds while traversing modern roudabouts based on geometric design characteristics. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch Univeristy [online]. Available: https://scholar.sun.ac.za/items/b566a71f-76a4-4a74-b740-d53a78ce0e30